BRAIN HEMISPHERE FUNCTION OF MALE AND FEMALE ENGLISH DEPARTMENT STUDENTS OF STKIP-MB: NEUROLINGUISTICS PERSPECTIVE - SUSANTI, SUSI (Journal Of Language Education and Development (JLed), 2018)
This research identifies brain hemisphere function of male and female English department students of STKIP-MB. It identifies the dominant of brain hemisphere’s male and female students. Those dominant of brain hemisphere can be guidance to optimize both hemisphere in order to get the success life. The result found the differentiation of brain hemisphere function between male and female students: 71,4% male students dominant left hemisphere, and 28,5% dominant right hemisphere; and 71,4% female students dominant right hemisphere, and 28,5% equal left hemisphere and right hemisphere. Neurologically, Male has corpus collosum which is smaller than female so male speaks directly and literally. Then, male has smaller lobus temporal, it causes male be talk less and to the point. Amigdala places in left hemisphere, it causes male cannot express something sentimentality. Seretonim and oxytocin in male are less, it makes male be more impulsive. Although, female has bigger limbic system than male. It makes female be more sentimental and expresses the feeling easier. Then, female’s amigdala places in right hemisphere, it causes female be sensitive and can produce the speech politely. Female has bigger corpus collosum about 25% when they are mature, it causes female can optimalize both of hemispheres, left and right hemisphere equally. Female has bigger lobus frontal and lobus temporal, it causes female be talkative and no straight to the point.